New agendas in statebuilding : hybridity, contingency and history - Egnell, Robert.; Haldén, Peter. (Routledge studies in intervention and statebuilding, 2013)
"This volume connects the study of statebuilding to broader aspects of social theory and the historical study of the state, bringing forth new questions and starting-points, both academically and practically, for the field. Building states has become a highly prioritized issue in international politics. Since the 1990s, mainly Western countries and international institutions have invested large sums of money, vast amounts of manpower, and considerable political capital in ventures of this kind all across the globe. Most of the focus in current literature is on the acute cases, such as Afghanistan and Iraq, but also to states that seem to fit the label 'failed states' such as Liberia, Sierra Leone and Somalia. This book brings together a diverse group of scholars who introduce new theoretical approaches from the broader social sciences. The chapters revisit historical cases of statebuilding, and provide thought-provoking, new strategic perspectives on the field. The result is a volume that broadens and deepens our understanding of statebuilding by highlighting the importance of hybridity, contingency and history in a broad range of case-studies. This book will be of much interest to students of statebuilding and intervention, peacebuilding, war and conflict studies, security studies and IR in general"--